Movers School Teachers' Perceptions of the Implementation of Merdeka Belajar Curriculum in the Central Ternate Paud Cluster - Wondal, Rosita; Mahmud, Nurhamsa; Arfa, Umikalsum; Oktaviani, Winda; Djaenal, Nurhikma A (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
This study aims to determine the Perceptions of Movers School Teachers Regarding the Implementation of Merdeka Belajar Curriculum in the Central Ternate PAUD Unit. This research is a descriptive qualitative research, with the research subjects being 6 PAUD teachers who have carried out the government program 'driving school' in Central Ternate. Data collection techniques in this study were carried out by observation, interviews, and documentation, with analysis techniques: data reduction, data display, and verification. The results of the research found that 1). Central Ternate PAUD driving school teachers have a positive perception and get a very good appreciation of the Merdeka Belajar curriculum. Teachers see this independent learning curriculum as an opportunity to provide diverse, creative, and interesting learning experiences for children. 2). There are several factors that become challenges, namely, first, the inadequate quality of the teacher's human resources, second, minimal learning facilities and resources or inadequate infrastructure.